Benthic Profile of the Proposed Marine Protected Area no. 4 Island Garden City of Samal - Cozo, Maian J.; Chavez Jr., Felix C. (JPAIR Multidisciplinary Research, 2008)
This study was conducted to determine the benthic profile of the proposed marine protected area no. 4, in Island Garden City of Samal. There are 44 coral genera identified and the area is commonly dominated by these coral genera, namely:Acanthastrea, Acropora, Anacropora, Coscinarea, Cycloseris, Cyphastrea, Echinophyllia, Echinopora, Euphyllia, Favia, Faviidea, Favites, Goniastrea, Heliofungia, Merulina, Mycedium, Physogyra, Pocillopra, Porites, Symphyllia, Lobophytum, Sarcophyton, Heliopora, Sympodium, and Cespitularia. The genus evenness is considered low due the patchy distribution of corals, while the genus richness of the coral reef is observed to be high based on the number of coral genera identified. The current environmental conditions such as physical and chemical factors are found to be fair and moderate, and suitable for the growth and reproduction of several corals. The abundance of small reef dwelling fishes indicates that the coral reefs are healthy and diverse. Larger pelagic and commercially important fishes such as groupers and snappers were also common based on the interview but rarely observed during the survey. The economic factors attest no detrimental effects to the coral reef and other marine organisms. In general, proposed marine protected area no. 4 is estimated to have 58 percent of live coral cover and 79 percent for its total coral cover.
Keywords: Coral reef; Coral diversity; Corals; Bethic; IGACOS; marine protected area